Interactive Media Based on Articulate Storyline to Improve IPAS Learning Outcomes - Maylani Mustikawati; Barokah Isdaryanti (Postgraduate, University of Mataram, 2024)
This study aims to develop, test the feasibility, and effectiveness of articulate storyline-based interactive media.Type of research and development (R&D) development research with ADDIE development model, namely analysis, design, development, implementation, and evaluation.Research subjects were grade IV students totaling 31 children.Data collection techniques with observation, interviews, questionnaires, and documentation data.The results of media expert validation show a percentage value of 86.6% very feasible category,material experts with a percentage value of 95% very feasible category.The results of the average value of pretests and posttests of students show an increase of 20.8 with an N-Gain value of 0.6 in the moderate category.Conclusion of the research results is the implementation of the use of interactive media based on articulate storyline with ADDIE development model is feasible and effective to improve IPAS learning outcomes of fourth grade students of SD Negeri Klepu 01.